Team Software Process (TSPI) Web-Based Support Too - Nurfauza, Jali; Cheah, Wai Shiang; Azman Bujang, Masli; Yanti Rosmunie, Bujang; Abdul Rahman, Mat; Suriati Khartini, Jali; Norazian, Mohd Hamdan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
One of the goals as a system or software developer that need to be achieved is to produce a product or system that can be considered as a high-level quality of a product. To help the developer produce a good quality of a product, a tool that will help them make their work easier and efficient is needed. TSPi Tool is one of the methods that can be used by the developer to plan their project, record the project progress, record defect and solve the defects. Currently, FCSIT students who're taking the Software Engineering and Laboratory are using the TSPi Support Tool (Excel Version). However, there are problems exists such as time-consuming which affects the progress of the project. The proposed solution for arising problems was the Team Software Process (TSPi) Tool Web-Based System, a web-based management system to manage and monitor the progress of the product development.